Komparasi Analisis Bukti Digital Tiktok Lite Menggunakan Metode National Institute of Justice - Rian Mailangkay, Imanuel Gilbert; Hadi, Abdul; Zakharia, Elia (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2022)
With the development of communication and information technology today, there are many applications to send information to each other or share information. Tiktok Lite or commonly called the light version of Tiktok is the same application as Tiktok but is more friendly for users who have low smartphone specifications. With all the features that TikTok Lite has, such as the feature of creating, editing, and sharing short video clips complete with filters and accompanied by music as support and sending text messages or chatting. This can have a negative impact on the use of Tiktok Lite because it can provide opportunities to commit crimes, especially cyberbullying. In overcoming this cyberbullying act, digital forensic analysis is needed on the Tiktok Lite application. The method used is the National Institute of Justice (NIJ), with the flow of Identification, Collection, Examination, Analysis, and Reporting. Based on the research results, the MOBILedit Forensics Express tool gets a percentage of 0% in the search for digital chat evidence and account data on the Tiktok Lite application on smartphones that have not been and have been rooted, while the Belkasoft Evidence Center and Magnet Axiom tools get a 100% percent in the search for digital evidence. chat and account data on the Tiktok Lite application on a smartphone that has been rooted.